2021
DOI: 10.3390/ijerph18147502
|View full text |Cite
|
Sign up to set email alerts
|

Community-Level Participation in Volunteer Groups and Individual Depressive Symptoms in Japanese Older People: A Three-Year Longitudinal Multilevel Analysis Using JAGES Data

Abstract: Background: The current study aimed to investigate the contextual effect of volunteer group participation on subsequent depressive symptoms in older people. Methods: We analyzed the longitudinal data of 37,552 people aged 65 years and older in 24 municipalities surveyed in the Japan Gerontological Evaluation Study. Volunteer group participation of older people was assessed in 2013 by one question and depressive symptoms were assessed by the Geriatric Depression Scale 15 in 2016. To investigate a contextual eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 32 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…Social participation is reported to have a preventive effect on the onset of depression. 26,27 Among older residents in a district of Tokyo, Okamura et al reported that between 2018 and April 2020, when the first state of emergency was declared, the proportion of people with depressed mood There were several limitations to this study. First, the study was conducted in a single city in Japan, and the results may have been affected by factors such as local characteristics of the COVID-19 epidemic and the extent of resumption of social participation.…”
Section: F I G U R E 1 Flowchart Of the Study Participantsmentioning
confidence: 89%
See 2 more Smart Citations
“…Social participation is reported to have a preventive effect on the onset of depression. 26,27 Among older residents in a district of Tokyo, Okamura et al reported that between 2018 and April 2020, when the first state of emergency was declared, the proportion of people with depressed mood There were several limitations to this study. First, the study was conducted in a single city in Japan, and the results may have been affected by factors such as local characteristics of the COVID-19 epidemic and the extent of resumption of social participation.…”
Section: F I G U R E 1 Flowchart Of the Study Participantsmentioning
confidence: 89%
“…Social participation is reported to have a preventive effect on the onset of depression. 26 , 27 Among older residents in a district of Tokyo, Okamura et al reported that between 2018 and April 2020, when the first state of emergency was declared, the proportion of people with depressed mood increased from 29% to 38%, and the proportion of people with frailty increased from 10% to 16%. 28 In our study, the prevalence of depressed mood was 20.8% in the Continued group and 37.4% in the Discontinued group, while it was 24.2% and 35.4% for oral frailty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, formal volunteering can be also viewed as a contextual phenomenon, a collective characteristic of groups that may independently affect health (Meng & Chen, 2014; Murayama et al, 2015; Tamura et al, 2021). Community‐level formal volunteering facilitates collective action and fosters norms of mutual trust and reciprocity (Kawachi et al, 1999).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The positive effects of volunteering on the health of older adults have been reported worldwide: 1 they include stress reduction, 2 alleviation of depressive moods, 3,4 improved physical health, 5,6 increased life expectancy, 7,8 improved quality of life, 9 and reduced mortality 10 . It has also been suggested that older adults receive more benefits than other age groups from volunteering 11,12 .…”
Section: Introductionmentioning
confidence: 99%